Inovasi Teknologi Digital dalam Meningkatkan Pengalaman Wisatawan di Destinasi Cerdas - Zahira Alifah Kirana (Tourism and Hospitality Research, 2025)
The rapid development of digital technology has significantly influenced the tourism industry, particularly in the concept of smart destinations. This study aims to analyze the role of digital innovations such as mobile applications, virtual reality (VR), augmented reality (AR), big data, and artificial intelligence (AI) in enhancing tourist experiences. Employing a qualitative approach with literature review and case study methods, this research explores how smart destination strategies are implemented in various countries. The findings reveal that digital innovations improve tourist engagement, provide personalized services, and facilitate sustainable tourism management. For instance, the integration of AR-based guides and AI-driven recommendation systems has been shown to enhance satisfaction and encourage repeat visits. Furthermore, big data analytics contribute to better decision-making for destination managers by predicting tourist behavior patterns. This study concludes that digital technology not only enriches tourist experiences but also supports competitiveness and sustainability in smart tourism destinations. Future research is recommended to focus on integrating digital innovations with local community participation to ensure inclusivity and long-term benefits.